DEVELOPING STUDENTS’ CREATIVITY IN TEACHING TEYL SUBJECT DURING COVID-19 PANDEMIC - Auraningrum, Zakia; Nurhajati, Diani; Sulistyani, Sulistyani (Universitas Muhammadiyah Metro, 2022)
The COVID-19 pandemic has influenced the education world, especially teaching and learning. Students must be equipped with four skills to survive in the global competition of the 21st century, namely Collaboration, Critical Thinking, Creativity, and communication (4C). One of the essential skills is creativity. Teachers have to provide learning activities for students to develop their skills. As a result, teachers must adapt to the condition by selecting the appropriate strategies. One of the strategies which can be applied during the pandemic is Project Based Learning. This study aims to describe the process of developing creativity in the students using Project Based Learning in the Teaching English to Young Learners (TEYL) course and the student's responses towards the strategy applied by the lecturer. This study is qualitative; the data were collected by documentation, observation checklist, and interviews. The subjects are lecturers and students taking TEYL courses for the 2020/2021 academic year. This study found that the lecturer employed blended learning to implement the teaching and learning process. She assigned the students a project: learning activities for young learners in the form of a book chapter. Through creating the project in TEYL courses, the students could develop their creativity, especially in fluency, flexibility, originality, and elaboration.